2023
DOI: 10.1111/1365-2664.14397
|View full text |Cite
|
Sign up to set email alerts
|

Native vegetation embedded in landscapes dominated by corn and soybean improves honey bee health and productivity

Abstract: Balancing demand for food while supporting biodiversity and ecosystem services in landscapes committed to crop production may require integrating conservation with agriculture. Adding strips of diverse, native, perennial vegetation, through the recently created prairie strips practice of the U.S. Conservation Reserve Program, into annual cropland reduces soil and nutrient loss, and supports more diverse and abundant communities of birds and insects, including native pollinators. It remains unclear if prairie s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Of the sown species, grey-headed coneflower, black-eyed Susan and Ohio spiderwort produced the most blooms by 2023. Since these were mostly summer-flowering species, such a bloom distribution was not ideal, especially given previous research suggesting pollinators' need for both early spring and late summer/fall floral resources [33]. Planting strategies like those investigated by [22] where early, mid, and late season-flowering WFs are planted in small monocultures might encourage a more favorable seasonal distribution of flower production that would benefit more pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…Of the sown species, grey-headed coneflower, black-eyed Susan and Ohio spiderwort produced the most blooms by 2023. Since these were mostly summer-flowering species, such a bloom distribution was not ideal, especially given previous research suggesting pollinators' need for both early spring and late summer/fall floral resources [33]. Planting strategies like those investigated by [22] where early, mid, and late season-flowering WFs are planted in small monocultures might encourage a more favorable seasonal distribution of flower production that would benefit more pollinators.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to maintaining preexisting diversity, restoring natural diversity in agricultural landscapes can increase the volume of food available: An experiment performed by Zhang et al (2023) examining prairie strips in an agricultural landscape found that honeybees collected 50% more pollen and colonies were 24% larger at the end of season monitoring. Many of the resources in the strips were left uncollected, meaning there was the potential capacity to provide food for other species.…”
Section: Nutrition and Stressor Resistancementioning
confidence: 99%
“…To find out the impact of various environmental stressors, air quality-related, on honey bee colonies, our analysis incorporated a range of environmental factors that contribute to the decline of bee populations 6,7,[13][14][15][16] , including the daily Air Quality Health Index (AQHI) 17 , daily average temperature, daily total precipitation, daily mean wind speed, and an index measuring vegetation intensity (NDVI) (see Methods for further details). In addition, we employed anonymized data with a sample size of over 29,044 hives covering 5,000 sites tracked over two seasons across North America from 2020 to 2022 (Extended Data Fig.…”
Section: Mainmentioning
confidence: 99%
“…Furthermore, the study highlights the significance of prolonged foraging hours in response to suboptimal air quality. It emphasizes the link between sustained pesticide exposure and its subsequent impact on honeybees 14,[42][43][44][45] , evident up to 48 hours after adverse air quality events. Here, we present a risk map for honey beehives in 2023 (Fig.…”
Section: Fig 2 | Variable Importance (Vimp) Using Random Survival For...mentioning
confidence: 99%
See 1 more Smart Citation